Land use changes analysis of Trakai Historical National Park in Lithuania - Visockiene, Jurate Sužiedelyte; Tumeliene, Egle; Bražiunas, Rokas (Advances in Geodesy and Geoinformation, 2024)
Remote sensing technology and the Earth system data it can obtain can provide great support for the monitoring and management of protected areas. These data can provide the ecological indicators of a place. It is very important to understand the situation concerning the natural land elements of a pro-tected area and to stop unacceptable actions in time. This paper presents an analysis of the natural elements of the land use/land cover (LULC) in the landscapes of protected areas. Freely available Sentinel-2A (S2A) multispectral data were used to classify the LULC and monitor the situation of protected areas. The research object was Trakai Historical National Park, which is an authentic land-scape in Lithuania. First, the Sentinel-2A image was processed and classified using the random forest algorithm by the special Lithuanian remote monitoring data collection, processing, use and storage system of the Environmental Protection Agency Lithuania. Next, the LULC model was statistically analysed using Quantum Geographic Information System (QGIS) software. The authors recommend automating these processes. The results show that in the period from 2021–2022, the farmland areas (cultivated meadows, decay areas, winter cereals, intensive cultivated crops and natural meadows) in Trakai Historical National Park decreased by 9.2%. Meanwhile, the forest, water and wetland areas increased by 9.6%, which makes it possible to conclude that these changes are beneficial for the ecosystems in this area.